Response to "Letter to the Editor: Vaccine Failures in Pediatric Cases Caused by Streptococcus pneumoniae Serotype 19A" - Erdem Gönüllü; Ahmet Soysal; İsmail Yıldız; Gökhan Aydemir; Turan Tunç; Metin Karaböcüoğlu (Taylor & Francis Group, 2020)
We are happy to answer to the Letter from Ozkaya-Parlakay et al. to the Editor commenting on our recent paper, 1 Â investigatedÂ impact of the 13-valent pneumococcal conjugate vaccine (PCV13)Â Â on the incidences of community-acquired pneumonia and pneumonia-related hospitalizations in children â‰¤5 years after its implementation into the national immunization program (NIP) of Turkey. Â Â Ozkaya-Parlakay et al. draw attention to vaccine failure and importance of continuous Â surveillance of relevant disease especially in the perspective of Â Streptococcus pneumoniae Â serotype 19A. They supported their opinion by their clinical observation of seven children who were vaccinated with PCV13 developed empyema and meningitidis caused byÂ Streptococcus pneumoniae Â serotype 19A   in Turkey.